2010
DOI: 10.1108/ijsms-11-03-2010-b002
|View full text |Cite
|
Sign up to set email alerts
|

Doping in elite sport - do the fans care? Public opinion on the consequences of doping scandals

Abstract: There are indications that commercial stakeholders are reluctant to associate with sports involved in doping scandals. A survey of 925 Norwegian sports consumers supports this reluctance, showing no tolerance for pure doping substances. The majority were in favour of tough responses to athletes and sports involved in doping. Older respondents were more negative towards doping. Those who were strongly interested in sport were more willing than others to accept doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 14 publications
4
40
1
3
Order By: Relevance
“…(Zeigler, 2007;p.303) Thus, one commercial marketing application of sport management becomes developing strategies that increase attendances at sporting events. In such a context, a problem such as doping by athletes represents both a threat and an opportunity: a threat in that doping might deter attendances (Engelberg, Moston, & Skinner, 2012) or threaten sponsorship (Solberg, Hanstad, & Thøring, 2010); an opportunity in that it might encourage even greater attendances through athletes who run ever faster, hit and throw ever further (Cashmore, 2012). In this latter case, the main purpose of athletic sport becomes the bettering of previous performances, with top athletes only truly achieving success if they can establish new records.…”
Section: 'Dark Side' Researchmentioning
confidence: 99%
“…(Zeigler, 2007;p.303) Thus, one commercial marketing application of sport management becomes developing strategies that increase attendances at sporting events. In such a context, a problem such as doping by athletes represents both a threat and an opportunity: a threat in that doping might deter attendances (Engelberg, Moston, & Skinner, 2012) or threaten sponsorship (Solberg, Hanstad, & Thøring, 2010); an opportunity in that it might encourage even greater attendances through athletes who run ever faster, hit and throw ever further (Cashmore, 2012). In this latter case, the main purpose of athletic sport becomes the bettering of previous performances, with top athletes only truly achieving success if they can establish new records.…”
Section: 'Dark Side' Researchmentioning
confidence: 99%
“…The Report provides a figure of AUS$8.82 billion for the 'total annual income generated [in 2006] by the sport and recreation industry' [The Importance of Sport in Australia, p. 10] and suggests that PIED use may result in a 'loss of faith in sport' by spectators which in turn could impact negatively on the financial value of Australian sport. The potential impact of doping on sports audiences is discussed by Carstairs (2003), Morgan (2009) and Solberg et al (2010) each of whom draws somewhat different conclusions as to the likelihood that doping will reduce the audience (in person or on TV) for sporting events. These debates aside, while this monetary figure is impressive it is followed by the more prosaic and familiar story of Australian values as espoused through sport.…”
Section: Methodsmentioning
confidence: 99%
“…A more specialized investigation by Engelberg, Moston, and Skinner (2012) indicated that the majority of the general public believed that sports teams should be penalized if members of their club were linked to performance-enhancing drugs. Moreover, scholarship by Soldberg, Hanstad, and Thoring (2010) suggested that public opinion favored: "strict reactions from sponsors towards athletes and sports involved in doping" (p. 197). All things considered, it appears the average sports consumer has limited tolerance for athletes who are associated with performance-enhancing measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature has revealed that the general public is rather critical of athletes and entities who are in any way associated with performance-enhancing substances (e.g. Engelberg, Moston, & Skinner, 2012;Paccagnella & Grove, 1997;Soldberg, Hanstad, & Thoring, 2010). At the same time, previous scholarship has not sufficiently scratched the surface with regard to parceling out whether different ethnicities maintain different ethos perceptions of athletes who reportedly foray with performanceenhancers.…”
Section: The Current Researchmentioning
confidence: 99%